DIAMETER SEL PURKINJE TIKUS (Rattus wistar L) SETELAH DIINDUKSI AIR TERCEMAR LIMBAH PENGOLAHAN BIJIH EMAS - Widya Sari; Sunarti ,; Mufidah Eka Putri (Universitas Islam Negeri Ar-Raniry, 2015)
The purpose of this research is to know the effect of mercury waste polluted water of traditional gold mining on cerebellum of fetal rat prenatal development. The water samples were taken from Rantau Panyang village and Paya seumantok village, Krueng Sabee District, Aceh Jaya. There were fifteen virgin female rat of wistar groove ten weeks old and 160 g Â± 10 g body weight in average and fifteen male rats 15 weeks old and 200 g Â± 20 g body weight in average were used as research objects. After female ratsinbreeded by single mating and positively pregnant in the first day, they were then directly treated. After that, they were divided into 3 treatments and five repetitions. The treatments were by giving aquadest as control (P0), river water (P1), and PDAM water (P2). Both river water and PDAM water were taken from gold mill at Krueng sabee, Aceh Jaya. The diameter of purkinje cell were analyzed by using anova and continued by Tukey test in the level of 5%. The result showed that the treatments could decrease the diameter of purkinje cells of fetus.